Party of two - Guillory, Jasmine (Berkley, 2020)
"A chance meeting with a handsome stranger turns into a whirlwind affair that gets everyone talking. Dating is the last thing on Olivia Monroe's mind when she moves to LA to start her own law firm. But when she meets a gorgeous man at a hotel bar and they spend the entire night flirting, she discovers too late that he is none other than hotshot junior senator Max Powell. Olivia has zero interest in dating a politician, but when a cake arrives at her office with the cutest message, she can't resist-it is chocolate cake, after all. Olivia is surprised to find that Max is sweet, funny, and noble-not just some privileged white politician she assumed him to be. Because of Max's high-profile job, they start seeing each other secretly, which leads to clandestine dates and silly disguises. But when they finally go public, the intense media scrutiny means people are now digging up her rocky past and criticizing her job, even her suitability as a trophy girlfriend. Olivia knows what she has with Max is something special, but is it strong enough to survive the heat of the spotlight?"--